The Role of Anticoagulant and Thrombolysis in The Management of Deep Vein Thrombosis - Anggia Endah Satuti; Hariadi Hariawan; Hasanah Mumpuni (ACI (Acta Cardiologia Indonesiana), 2015)
Deep vein thrombosis (DVT) is a clinical challenge encountered by clinicians of all specialties. The major complication to date is thrombus embolization into the lung which can be fatal. The mainstay of DVT therapy is an anticoagulant to prevent the thrombus development and recurrence. However, anticoagulant has no direct thrombolysis effect and recanalization of DVT largely depends on the effectiveness of the endogenous fi brinolytic system. Many agents are developed to improve the outcome and prevent a post thrombotic syndrome (PTS). The aim of this review is to give explanation on the use of anticoagulant, especially vitamin K antagonist, warfarin and thrombolytic therapy in DVT.